The perception of the income tax: Evidence from Germany - Denis Beninger (Verein für Socialpolitik, 2010)
The paper explores whether the tax rule defined by the tax law or the perception of the tax system by the single household matters in explaining household behaviour. In particular, Germany applies joint taxation with marital splitting to married couples. However, the couple has the choice between two formulas when paying the tax. In both cases, the perceived marginal tax rate, i.e. the rate which practically applies, and the real one, i.e. the one calculated from the tax function, differ systematically. Using the 2004 wave of the German Socio-Economic Panel, we find that (i) the perceived marginal tax rate is a better indicator than the real one when explaining the couples' behaviour, (ii) there is a correlation between income pooling and the system of tax collection chosen by the couple, and (iii) the intra-household bargaining rule depends on the specificities of the tax system.
Keywords: D12; H24; J22; 330; Collective model; taxation; intra household allocations